Reform and Development of Rare Diseases Drug Evaluation and Approval in China - HUANG Guo; YANG Zhimin; TANG Ling; ZHANG Jie; AI Xing; SE RI Geleng; ZHAO Tian (罕见病研究)
Rare diseases have a significant and profound impact on society, the economy, and the healthcare system. The path to developing drugs for rare diseases is particularly arduous. Due to the small number of patients and limited market demand, pharmaceutical companies don′t have enough incentives and resources to invest in drug research and development. Additionally, the long development cycles, high costs, and high risks have led to a number of potential therapeutic drug failures at the early stages of development. This article summarizes a series of encouraging policies adopted by the National Medical Products Administration for rare diseases, which is an important public health issue, as well as the achievements in the review and approval of rare disease drugs in recent years. These policies have accelerated the approval process. Meanwhile, the policies ensure the safety and effectiveness of drugs and offer more treatment options and hopes to patients with rare diseases. With the continuous effort at optimizing the policy environment and the advancement of research and development technologies, China′s drug regulatory authorities will continue to focus on the clinical needs of rare diseases, to implement " patient-centered " approach to drug development, inject new vitality into the research and development of drugs of rare diseases, and offer more precise and effective treatment choices for patients with rare diseases.